Overcoming Barriers to Integrating Circular Economy in Nigerian Infrastructure Design and Construction - Unegbu, Hyginus; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Journal of Sustainable Construction, 2026)
This study investigates the integration of Circular Economy (CE) principles into Nigerian infrastructure projects, identifying key barriers and proposing effective countermeasures. The research employed a mixed-methods approach, combining surveys and semi-structured interviews with 100 stakeholders, including policymakers, construction professionals, and academic experts. The analysis revealed significant barriers across economic, technical, policy, and social dimensions. Economic challenges included high initial costs and limited financial resources. Technical barriers were characterized by a lack of expertise and insufficient infrastructure for sustainable materials. Policy and regulatory obstacles highlighted inadequate policies and poor enforcement, while social barriers pointed to resistance to change and low awareness of CE benefits. Proposed countermeasures included implementing government incentives such as tax breaks and subsidies, fostering public-private partnerships to leverage combined resources and expertise, and launching education and awareness campaigns to build capacity and support for CE practices. The findings have significant implications for policymakers and industry stakeholders, emphasizing the need for a comprehensive national CE policy framework and collaborative efforts to promote sustainability. Future research should focus on the long-term impacts of CE integration and explore innovative solutions to overcome identified barriers.